2000
DOI: 10.1021/jo0012400
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Fluorine Migration via Four-Member Cyclic Transition States

Abstract: Gaseous CF(3)(+) interchanges F(+) for O with simple carbonyl compounds. CF(3)(+) reacts with propionaldehyde in the gas phase to produce (CH(3))(2)CF(+) via two competing pathways. Starting with 1-(13)C-propionaldehyde, the major pathway (80%) produces (CH(3))(2)CF(+) with the carbon label in one of the methyl groups. The minor pathway (20%) produces (CH(3))(2)CF(+) with the carbon label in the central position. The relative proportions of these two pathways are measured by (19)F NMR analysis of the neutral C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Mass spectrometric research on polyfluorinated compounds can provide important information for their structural assignment and enrich the knowledge of their gas‐phase reactivity for the chemists. Previous work showed that the unique mass spectrometric behaviors of these compounds include F‐atom migration, double F‐atom migration, F‐atom ring walk, and trifluoromethyl (CF 3 ) group rearrangement . Tajima et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometric research on polyfluorinated compounds can provide important information for their structural assignment and enrich the knowledge of their gas‐phase reactivity for the chemists. Previous work showed that the unique mass spectrometric behaviors of these compounds include F‐atom migration, double F‐atom migration, F‐atom ring walk, and trifluoromethyl (CF 3 ) group rearrangement . Tajima et al .…”
Section: Introductionmentioning
confidence: 99%
“…Morton et al . reported ion–molecule reactions of CF 3 + with carbonyl compounds, followed by F‐atom migration via four‐membered cyclic transition states . Speranza et al .…”
Section: Introductionmentioning
confidence: 99%
“…The structure of ion 4 in the gas phase has been confirmed by collection and identification of the neutral products from its subsequent ion-molecule reactions. [11] Because of the small number of atoms in 4, resonant IRMPD on this ion in the gas phase presents a challenge. For that reason, we have examined the perdeuterated analogue 5, for which the vibrational levels are more closely spaced.…”
mentioning
confidence: 99%
“…Furthermore, it has been demonstrated that 1,3-fluorine transfer operates in the reaction of CF 3 C with propionaldehyde in the gas phase, via a four-membered cyclic transition state. 8 In order to examine whether the F migration phenomenon occurs in other trifluoromethoxy-containing compounds, 4-(trifluoromethoxy)phenol was studied using the LCQ ion trap mass spectrometer and a similar CID fragmentation pattern was observed. Upon CID in the negative ion mode, 4-(trifluoromethoxy)phenol gave rise to three major fragments at m/z 155, 111, and 108 (Fig.…”
mentioning
confidence: 99%